CLASSIFICATION OF WHEAT YELLOW RUST POPULATIONS IN THE CONDITIONS OF KAZAKHSTAN - Shapalov Shermakhan Kuttibayevich; Tileubaeva Zhanar Slyamkhanovna; Makhambetov Murat Zharakovich; Yermekbayeva Akbope Tontaevna; Turgenova Oryngul Mukashevna; Issengalieva Gulya Amirzhanovna; Islamova Klara; Nurmukhanova Gulnara; Baidrakhmanov Dossym; Sagitova Guzaliya Faritovna (Scientific Journal of Pedagogy and Economics, 2019)
One of the most dangerous fungal diseases of cereals is the wheat yellow rust that causes Pucciniastriiformis West. f. sp. triticiErikss. et Henn. The yellow rust significantly reduces the yield and lowers grain quality. The occurrence of disease in autumn and its wintering during the vegetation period in favorable climatic conditions in the autumn wheat field leads to a 100 percent loss of crop. An important element in the integrated protection of wheat crops from rust disease is a variety. Success in selection of disease resistance depends on the population structure of pathogens, which differ from soil-climatic zones and biotic, abiotic factors. The article presents the results of yellow rust study in the South and South-Eastern Kazakhstan. The determined pathotypes are classified into three groups: high, middle and low (minimal) virulence. High virulence patterns of HeinesKolben, Lee Chinese 166, Heines VII and Reichersberg 4 were virulent to classifiers up to 100 percent.